2012
DOI: 10.1109/jproc.2012.2184830
|View full text |Cite
|
Sign up to set email alerts
|

Brain–Computer Interface Technologies in the Coming Decades

Abstract: As the proliferation of technology dramatically infiltrates all aspects of modern life, in many ways the world is becoming so dynamic and complex that technological capabilities are overwhelming human capabilities to optimally interact with and leverage those technologies.Fortunately, these technological advancements have also driven an explosion of neuroscience research over the past several decades, presenting engineers with a remarkable opportunity to design and develop flexible and adaptive brain-based neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(119 citation statements)
references
References 121 publications
(125 reference statements)
1
104
0
4
Order By: Relevance
“…This change in paradigm from "let the user learn" to "let the machine learn" largely reduced training times and significantly increased the attraction of these systems (Blankertz et al, 2006a). Although technology has rapidly advanced during the last decade, e.g., dry electrode EEG recordings (Popescu et al, 2007), zero training systems Fazli et al, 2009) and robust machine learning methods (Lotte and Guan, 2011;, many challenges limiting a large scale application of BCIs in clinical practice and its usage as assistive technology for disabled people still exists (Dietrich et al, 2010;Krusienski et al, 2011;Lance et al, 2012). Several pilot studies Lim et al, 2012) have demonstrated the utility of BCI for medical application, but much more research is needed in this direction.…”
Section: Part I R E V I S I T I N G B C Imentioning
confidence: 99%
“…This change in paradigm from "let the user learn" to "let the machine learn" largely reduced training times and significantly increased the attraction of these systems (Blankertz et al, 2006a). Although technology has rapidly advanced during the last decade, e.g., dry electrode EEG recordings (Popescu et al, 2007), zero training systems Fazli et al, 2009) and robust machine learning methods (Lotte and Guan, 2011;, many challenges limiting a large scale application of BCIs in clinical practice and its usage as assistive technology for disabled people still exists (Dietrich et al, 2010;Krusienski et al, 2011;Lance et al, 2012). Several pilot studies Lim et al, 2012) have demonstrated the utility of BCI for medical application, but much more research is needed in this direction.…”
Section: Part I R E V I S I T I N G B C Imentioning
confidence: 99%
“…It has shown potential applications in many fields: rehabilitation [1], [2], games [4], and military [5]. Event-related potential (ERP) is a type of brain signal defined as an electrical response of the cortex to stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…BCI allow users to communicate directly with their surroundings making use of their brain signals with the aid of systems like BCI Speller [1], [2]. Researchers have been using physiological data such as Electroencephalography (EEG), Electrooculography (EOG), Electromyography (EMG), Eelectrocorticography (ECoG), Electrodermal Activity (EDA), Blood Oxygen Saturation, Respiration, Skin Temperature etc.…”
Section: Introductionmentioning
confidence: 99%